Ectopic CD137 expression by rhabdomyosarcoma provides selection advantages but allows immunotherapeutic targeting. (1st January 2021) - Lee, Kang Yi; Wong, Hiu Yi; Zeng, Qun; Le Lin, Jia; Cheng, Man Si; Kuick, Chik Hong; Chang, Kenneth Tou En; Loh, Amos Hong Pheng; Schwarz, Herbert
ABSTRACT: Rhabdomyosarcoma (RMS) is a heterogeneous soft tissue neoplasm most frequently found in children and adolescents. As the prognosis for recurrent and metastatic RMS remains poor, immunotherapies are hoped to improve quality of life and survival. CD137 is a member of tumor necrosis factor receptor family and a T cell costimulatory molecule which induces potent cellular immune responses that are able to eliminate malignant cells. Therefore, it was puzzling to find expression of CD137 on an RMS tissue microarray by multiplex staining. CD137 is not only expressed by infiltrating T cells but also by malignant RMS cells. Functional in vitro experiments demonstrate that CD137 on RMS cells is being transferred to adjacent antigen-presenting cells by trogocytosis, where it downregulates CD137 ligand, and thereby reduces T cell costimulation which results in reduced killing of RMS cells. The transfer of CD137 and the subsequent downregulation of CD137 ligand is a physiological negative feedback mechanism that is likely usurped by RMS, and may facilitate its escape from immune surveillance. In addition, CD137 signals into RMS cells and induces IL-6 and IL-8 secretion, which are linked to RMS metastasis and poor prognosis. However, the ectopic expression of CD137 on RMS cells is an Achilles' heel that may be utilized for immunotherapy. Natural killer cells expressing an anti-CD137 chimeric antigen receptor specifically kill CD137-expressing RMS cells. Our study implicates ectopic CD137 expression as a pathogenesis mechanism in RMS, and it demonstrates that CD137 may be a novel target for immunotherapy of RMS.